Integration: Yes or No? Kindergarten teachers’ opinion about integration of children with special educational needs (Training and Practice : Journal of Educational Sciences, 2020)
In the last few years, the number of kindergarten age children with special educational needs has constantly risen. In parallel, the number of integrated children in Hungarian kindergartens has also grown (KSH educational data). Because of this, successful integration is becoming more and more important. One of the most important subjective conditions of the integrated education is the teacher as such (Csányi, 2000). Therefore, in my research, looking for coherency among other things, I asked kindergarten teachers how they see integration in 2020, and how they rate their basic kindergarten training in the aspect of special educational needs. The results show that 72% of the respondents think that integration is difficult for them to manage. The point-biserial correlation has shown that experience does not make integration easier (p = 0.36). Another outcome of this research is that, for the kindergarten teachers, children with autism spectrum disorder are the most challenging to integrate.